Range shifting on fragmented landscapes - McInerny, Greg; Travis, J.M.J.; Dytham, C. (Ecological Informatics, 2007)
Projected responses of species' to climate change have so far included few of the factors that are important determinants of species' distributions within its range. In this paper we utilise a spatially explicit cellular lattice, colonisation–extinction model to investigate the effect of habitat loss, fragmentation and species characteristics on range shifting in response to climate change. Contrary to the predictions of patch occupancy in static climate models we show that fragmentation can have a positive effect on species survival when species have high colonisation rates. For species with low colonisation rates aggregative behaviours prevent success on fragmented landscapes at high levels of habitat loss, and range shifting is more successfully achieved where habitat is correlated. At levels of habitat loss near the extinction threshold, less fragmented landscapes can facilitate range shifting even for the best colonisers. We discuss how imposing a climate window may reduce percolation routes and have implications for the area of usable habitat at any given level of habitat availability. We demonstrate the importance of landscape structure for range shifting dynamics and argue that management of reserve networks needs to consider the requirements of species with different life history characteristics.
http://www.sciencedirect.com/science?_ob=ArticleURL&_udi=B7W63-4N517CY-1&_user=10&_rdoc=1&_fmt=&_orig=search&_sort=d&_docanchor=&view=c&_searchStrId=957151328&_rerunOrigin=scholar.google&_acct=C000050221&_version=1&_urlVersion=0&_userid=10&md5=dab8254f4fc6a6895cffa96e644e8a9a